Houses of the unholy ebook - Brubaker, Ed (Image Comics, 2024)
An FBI agent from the cult crime beat and a woman with a past linked to the Satanic Panic are drawn into a terrifying hunt for an insane killer hiding in the shadows of the underworld. Can you ever escape your past, or are all your bad decisions just more ghosts to haunt you, wherever you go? HOUSES OF THE UNHOLY is a riveting horror thrill ride from bestselling creators ED BRUBAKER and SEAN PHILLIPS, the award-winning team behind CRIMINAL (soon to be a TV series on Amazon Prime), RECKLESS, NIGHT FEVER, and WHERE THE BODY WAS.